The role of plant-crab interaction in structuring microphytobenthic communities in a shallow temperate estuary - Fernandez, Carolina (2018)
Microphytobenthos can be defined as the assemblage of microscopic, photosynthetic eukaryotic microalgae and cyanobacteria that live on sediment surfaces in salt marshes, submerged aquatic vegetation beds, intertidal sand and mudflats, and subtidal, illuminated sediments (MacIntyre et al., 1996; Miller et al., 1996). These microorganisms produce macroscopically recognizable microbial mats dominated by cyanobacteria and biofilms of epipelic diatoms, these structures are the result of sediment trapping, binding and precipitation by the extracellular polymeric substances (EPS) produced by the microorganisms (de Winder et al., 1999).